Oral health promotion and homelessness: A theory-based approach to understanding processes of implementation and adoption. (March 2016) - Beaton, Laura; Freeman, Ruth
Objective: To use the Theory of Diffusion of Innovations as a framework to explore the qualitative data gleaned from a process evaluation of the Smile4life intervention across Scottish National Health Service (NHS) Boards and to inform future oral health promotion and homelessness. Design: A qualitative exploration. Setting: In 2012, the Smile4life programme to promote the oral health of homeless people was launched in Scotland. Practitioners received training to ensure its successful implementation and adoption. A process evaluation began in February 2013. Method: A total of 20 oral health officers from the 11 participating NHS Boards took part in the process evaluation. They were interviewed each month for a 17-month period. Boards were placed into adoption categories based on the time taken to adoption. The data were analysed using a framework approach. Results: The Theory of Diffusion of Innovations was used to define 'time to adoption' and to classify participating NHS Boards' adoption categories. It was also used to identify diffusion variables that underpinned Smile4life adoption. For Boards that more readily adopted Smile4life, the diffusion variables of familiarity and good social exchanges appeared to promote implementation. Numerous conflicts emerged, however, in late adoption Boards. These included a lack of resources and practitioner ambivalence, which slowed up implementation. Conclusion: The Theory of Diffusion of Innovations provided a useful theoretical framework for understanding the processes in the implementation and adoption of the Smile4life programme. It allowed specific training requirements for the practitioners to emerge to facilitate diffusion of the programme in their Boards.